Seed Priming: A Promising Technology for Higher Production - Nagarjuna, Polagani; Veerendra, M. (Research Advances and Challenges in Agricultural Sciences Vol. 9, 2024)
A higher percentage of seed germination and early and vigorous seedling growth leading to uniform plant stand is crucial for better growth and development of the crop. The influence of any crop management practise to increase the yields can’t exceed the limits set by the seed. Seed germination and seedling growth is affected by several factors operating simultaneously in the field finally resulting in variation in crop yield. Major factors include abiotic and biotic stresses. Seed priming, an ancient yet effective technique can address this issue of poor germination and uneven crop stand under stressful situations. This strategy can be used in conjunction with appropriate field management approaches to improve seed quality and germination. Many researchers have studied seed priming in different field crops and realised yield and economic benefits. This chapter helps in understanding the technique of seed priming in detail and its mechanism in improving the yields.